PHP Crash Course Learn PHP in 90 Minutes - Taulien, Kalob (Packt Publishing, 2020)
Learn PHP in less than 90 minutes with this fast-paced PHP guide About This Video Get up to speed with writing PHP code and explore basic concepts of PHP and its uses Understand how to use fundamentals such as variables, data types, and strings to create projects Work with arrays, loops, statements, and operators to simplify the code in PHP and other languages In Detail This PHP course is designed to get you started quickly with the fundamentals of PHP and using PHP to write code. While the course features detailed concepts, its organized structure and concise explanations ensure rapid yet effective learning. In an interactive style, the course demonstrates the installation of PHP on your computer. After this, you'll be on your way to creating a robust PHP file. Gradually, you'll gain insights into what PHP is, the different PHP users, and their purpose for using the language. The course later progresses to covering the fundamentals that will help you in learning other programming languages. This includes variables, constants, data types, loops, multidimensional arrays, functions, super global variables, and forms. By the end of this course, you will be well-versed with PHP and be equipped with the skills you need to write clean PHP code.